Analisis Mendalam Bahaya Polusi Udara dan Upaya Pencegahan Preventif yang Efektif - Shofa Aprilia Zahara; Ade Rita Suryani Siregar; Marniati Marniati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Air pollution is one of the major public health challenges in Indonesia. This article analyzes the characteristics of main pollutants, emission sources, health impacts, and prevention strategies that have been and are being implemented. Based on secondary data from various government reports, scientific journals, and recent case studies, it was found that emissions from the transportation sector, industry, biomass burning, and forest fires remain the main contributors to air pollution. The impacts include increased incidence of respiratory infections, chronic lung disease, cardiovascular disorders, and economic losses. Preventive efforts such as the adoption of electric vehicles, vehicle emission inspections, and citizen science programs have proven effective but need to be expanded. This article recommends the integration of cross-sectoral policies, the use of modern monitoring technologies, and sustainable public education.